The Role Of Gas Turbine In Utilizing Earth Gas And Oil As A Power Energy Generator; Problem And Solution - Ari Yuneldi (Teknik Informatika, Universitas Pelita Bangsa, 2021)
The existence of gas turbines has an important role in generating energy, this tool utilizes gas and oil fuels to produce energy that is ready for use. Gas turbines continue to experience modifications and developments from year to year so that they can be used effectively and efficiently in their operation. Various technologies are developed to be able to generate electrical energy to the maximum by modifying and combining one working principle with other work principles. Whatever the facts are as sophisticated as any technology that is developed still has weaknesses and shortcomings so it requires more time to be able to produce a quality product. Therefore we need a process of innovation and problem solving in order to overcome this problem by providing alternative solutions to the shortcomings that exist so that the technology used can generate various benefits and minimize the risk of loss. In this report there are several alternative solutions for technology and generator components that are expected to provide little input and solutions so that among some of the shortcomings can be minimized. Keywords: Gas turbines, electrical energy, energy generation technology, gas and petroleum, alternative solutions